Perkembangan Otak dan Fungsi Kognitif Anak: Peran Nutrisi dan Sistem Imun pada Awal Kehidupan - Rahmi Novita Yusuf; Helmi Helmi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The human brain has about 86 billion neuron cells, which have the function of sending signals or impulses to and from the brain. The brain is a vital organ in human survival. The human brain begins to form in the middle of the first trimester of pregnancy. This type of research uses the literature review method sourced from published journals related to brain development and cognitive function of children; the role of nutrition and the immune system at the beginning of life. All journals and articles are obtained from: Pubmed, PMC, Google Cendikia with journal inclusion criteria that discuss the immune system ( microglia, pro-inflammatory cytokines IL-1β, α, IL-6, TNFα) cognitive function, child brain development ( Precursor neurotrophic factors (BDNF), nerve growth factors (NGF)), and nutrition ( Intestinal microbiota, modified cassava flour (MOCAF)) which are full texs. The result of this study is that the microbiota has a function in the process of absorbing nutrients, Both macronutrients and micronutrients needed by the fetal brain for the development of function. Mocaf consumption also plays a role in the absorption of calcium needed by the fetal brain for the process of neurogenesis, synaptogenesis. Gut microbiota imbalances have been shown to play a role in impaired brain development and cognitive function in ASD children. In addition to nutrition, the microglia system in the immune system also plays a big role as the main element of brain development and cognitive function. Microglia dysfunction in the central nervous system triggers proinflammatory cytokines through ROS so it is shown to have affected neurogenesis, synaptogenesis, cell mykgration, neuron cell life and triggered neurodegenerative diseases in subsequent offspring.